2014
DOI: 10.5194/bgd-11-4531-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Morphology of <i>Emiliania huxleyi</i> coccoliths on the North West European shelf – is there an influence of carbonate chemistry?

Abstract: Abstract. Within the context of the UK Ocean Acidification project, Emiliania huxleyi (type A) coccolith morphology was examined from samples collected during cruise D366. In particular, a morphometric study of coccolith size and degree of calcification was made on scanning electron microscope images of samples from shipboard CO2 perturbation experiments and from a set of environmental samples with significant variation in calcite saturation state (Ωcalcite). One bioassay in particular (E4 from the southern No… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 38 publications
2
23
1
1
Order By: Relevance
“…In addition, the present study is only based on a single strain of Southern Hemisphere E. huxleyi. Due to the wide distribution of this species in the natural marine environment, E. huxleyi presents high variability in terms of genetic, morphological, and physiological characteristics (Cook et al, 2011;Read et al, 2013;Young et al, 2014). Therefore, the physiology of different E. huxleyi strains isolated from different geographic locations might respond differently to changing environmental drivers.…”
Section: Biogeochemical Implications and Future Directionsmentioning
confidence: 99%
“…In addition, the present study is only based on a single strain of Southern Hemisphere E. huxleyi. Due to the wide distribution of this species in the natural marine environment, E. huxleyi presents high variability in terms of genetic, morphological, and physiological characteristics (Cook et al, 2011;Read et al, 2013;Young et al, 2014). Therefore, the physiology of different E. huxleyi strains isolated from different geographic locations might respond differently to changing environmental drivers.…”
Section: Biogeochemical Implications and Future Directionsmentioning
confidence: 99%
“…The projected changes in the marine carbonate system will likely have profound biological consequences for oceanic and near-coastal ecosystems within the coming Marine Chemistry xxx (2015) xxx-xxx decades and centuries (Guinotte and Fabry, 2008) with anticipated detrimental effects on marine calcifiers (Fabry, 2008), corals (Hoegh-Guldberg et al, 2007), mollusks (Gazeau et al, 2013) and crustaceans (Whiteley, 2011), making it more difficult to build and maintain skeletons, tests, and shells of calcium carbonate (Doney, 2006). The effects of ocean acidification on coccolithophore calcification are not fully resolved and a topic of much debate (Iglesias-Rodriguez et al, 2008;Riebesell et al, 2000;Young et al, 2014) with reported species specific responses to ocean acidification (Langer et al, 2006). Furthermore, our understanding on the effects of ocean acidification on non-calcifying marine organisms, ecosystem diversity and biogeochemical processes is only just emerging (Gattuso et al, 2013;MacGilchrist et al, 2014;Raven et al, 2005;Richier et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…There is medium evidence and low agreement on how coccolithophore growth and calcification will be affected as they exhibit highly varied responses depending on species, strain and secondary environmental controls such as irradiance, bloom species composition and nutrient availability (Benner et al, 2013;Horigome et al, 2014;Muller and Nisbet, 2014;Poulton et al, 2014;Sett et al, 2014;Young et al, 2014). There is evidence that the coccolithophore, Emiliania huxleyi, has the capacity to evolve genetic adaptions to both warming and ocean acidification expected under RCP8.5 (Benner et al, 2013;Lohbeck et al, 2014;Schluter et al, 2014).…”
Section: Updates To Ar5mentioning
confidence: 99%